1999
DOI: 10.1046/j.1365-2249.1999.01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble Fas ligand in patients with silicosis

Abstract: Certain patients with silicosis have been reported to exhibit immunological abnormalities such as the appearance of antinuclear antibodies and the occurrence of autoimmune diseases. Fas ligand (FasL) is a type II membrane protein which induces apoptosis by binding to its membrane receptor, Fas. FasL is converted to a soluble form by a metalloproteinase-like enzyme. We have already found serum soluble Fas (sFas) levels in silicosis patients as well as in patients with systemic lupus erythematosus (SLE) to be si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 25 publications
3
38
0
Order By: Relevance
“…than in healthy donors (HDs), although the level of serum soluble Fas ligand did not differ between SPs and HDs (Tomokuni et al, 1997(Tomokuni et al, , 1999. The mean fluorescent intensity (MFI) of membrane 4.…”
Section: Silica Particles and Dysregulation Of Immune Response Leadinmentioning
confidence: 94%
“…than in healthy donors (HDs), although the level of serum soluble Fas ligand did not differ between SPs and HDs (Tomokuni et al, 1997(Tomokuni et al, , 1999. The mean fluorescent intensity (MFI) of membrane 4.…”
Section: Silica Particles and Dysregulation Of Immune Response Leadinmentioning
confidence: 94%
“…The causes of the fibrogenic effect of free crystalline SiO 2 are not completely clarified [5][6][7][15][16][17][18]. Disbalance in the immune response regulation is suggested [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…We found that dysregulation of the Fas-mediated apoptotic pathway might play an important role in the pathogenesis of the immunological abnormalities found in silicosis patients 7,8,[17][18][19] . Therefore, it is suggested that the genesis of anti-topo I autoantibodies is associated with the abnormalities of apoptosis-related molecules in silicosis patients.…”
Section: Discussionmentioning
confidence: 84%
“…Details of materials and methods for B (i), (iii), (iv) and (v) and B (vi) were previously reported by Tomokuni et al 7,17) and Otsuki et al 8) , respectively.…”
Section: Clinical Parameters Of Silicosismentioning
confidence: 99%